LEARNING STRATEGIES WHILE PLAYING AS A LEARNING METHOD FOR CHILDREN OF KAMPUNG BARU GUIDANCE STUDIO - Dewi Nurdiyanti; Tania Nurlia Hermawati; Tania Avianda Gusman; Indah Karina Yulina; Arif Nurudin; Muhammad Nana Trisolvena; johan; arie susetio utami; Norman Bastian; Desy Lusiana; Mutiara Dwi Cahyani (Ann Publisher, 2024)
Learning is developing knowledge, skills, and attitudes interactively. Learning while playing by children can provide opportunities to explore, practice, and get a variety of concepts. Learning while playing is fun and can attract and motivate children to achieve learning goals optimally. Learning activities while playing are carried out with a feeling of pleasure, without coercion, but have a method that is expected to create results that promote good development for children. Play activities are one of the stimulus factors in children's intelligence